SCHIZOPHRENIA IN HARRY POTTER AND SORCERER STONE NOVEL: Schizophrenia - Ernita Ndaung (Fakultas Sastra Universitas Gresik, 2021)
Schizophrenia is a mental disorder characterized by symptoms such as hallucinations and delusions. Schizophrenia is a syndrome that could induce seriously psychology problems. This novel tells of schizophrenia in a novel entitled Harry Potter and Sorcerer Stone. The main target in this story is Harry Potter.Researchers want to know how Schizophrenia occurs, then what are the factors and impacts of schizophrenia. The purpose of this study is to find out how schizophrenia occurs and its impact in the Harry Potter and the Sorcerer Stone novel.This study was designed in a qualitative manner using the explanatory method. Research data shows that Harry Potter has schizophrenia. Schizophrenia factor found in novels such as Dementors, Voldemort's Horcruxes, magic suppression, Bullying, Abuse Child. Furthermore, research shows that schizophrenia has a big impact on Harry Potter, namely being a famous wizard, having the love of his parents, and being a hero